Microsporidia Intracellular Development Relies on Myc Interaction Network Transcription Factors in the Host. Issue 9 (1st September 2016) - Botts, Michael R; Cohen, Lianne B; Probert, Christopher S; Wu, Fengting; Troemel, Emily R
Abstract: Microsporidia are ubiquitous parasites that infect a wide range of animal hosts, and these fungal-related microbes undergo their entire replicative lifecycle inside of host cells. Despite being widespread in the environment and causing medical and agricultural harm, virtually nothing is known about the host factors important to facilitate their growth and development inside of host cells. Here, we perform a genetic screen to identify host transcription factors important for development of the microsporidian pathogen Nematocida parisii inside intestinal cells of its natural host, the nematode Caenorhabditis elegans . Through this screen, we identified the C. elegans Myc family of transcription factors as key host regulators of microsporidia growth and development. The Mad-like transcription factor MDL-1, and the Max-like transcription factors MXL-1 and MXL-2 promote pathogen levels, while the Myc-Mondo-like transcription factor MML-1 inhibits pathogen levels. We used epistasis analysis to show that MDL-1 and MXL-1, which are thought to function as a heterodimer, appear to be acting canonically. In contrast, MXL-2 and MML-1, which are also thought to function as a heterodimer, appear to be acting in separate pathways (noncanonically) in the context of pathogen infection. We also found that both MDL-1::GFP and MML-1::GFP are expressed in intestinal cells during infection. These findings provide novel insight into the host transcription factors that regulate microsporidia development.